Inequality, Familial Aggregation, and Risk Prediction of Caries in Siblings. (October 2021) - Sengupta, K.; Ersbøll, A.K.; Christensen, L.B.; Mortensen, L.H.; Andersen, I.
Introduction: Social and family conditions are likely of great importance to dental health; however, limited evidence of familial aggregation of caries among adolescent siblings exists. Moreover, social and family-level factors have never been evaluated as isolated caries predictors at the individual level. Objectives: The objectives were to evaluate socioeconomic patterning of caries among siblings, assess sibling-specific aggregation of caries within families, and examine if such aggregation differed by parental socioeconomic position (SEP). We also evaluated the discriminant ability of sibling caries, SEP, and other social and familial factors in predicting caries in cosiblings. Methods: This nationwide register-based study included all 15-y-olds in Denmark in 2003 (index siblings) and their biological siblings born within ±3 y (cosiblings). Clinical and sociodemographic data for each subject were compiled from Danish national dental, social, and population registers. Caries was measured by the decayed, missing, and filled tooth surfaces (DMFS) index. Predictors included SEP (parental education, income, and occupational social class), gender, birth order, immigration status, and household type. Adjusted SEP-caries associations were estimated using negative binomial regression. Familial aggregation was evaluated using adjusted pairwise odds ratios from alternating logistic regressions. Caries prediction was based on classification and regression tree (CART) analyses. Results: The study included 23, 847 sibling pairs (n = 47, 694). Socioeconomic patterning of caries was similar among the index and cosiblings with significant graded SEP-caries associations. Significant sibling-specific aggregation of caries was observed; cosiblings of caries-affected index siblings had odds of having caries 3.9 times (95% confidence interval: 3.65–4.18) as high as that of cosiblings with caries-free index siblings. This sibling similarity was stronger in socioeconomically disadvantaged families (adjusted pairwise odds ratios: 3.08–5.47). CART revealed index sibling caries as the single most important caries predictor, with caries predicted in ≥84% of cosiblings of adolescents with ≥3 carious tooth surfaces. Conclusions: Caries in a sibling should prompt preventive family-based approaches targeting cosiblings. Knowledge Transfer Statement: This study revealed significant socioeconomic patterning of caries in adolescent siblings. Prediction modeling indicated that the single most important caries predictor among cosiblings was index sibling caries. Information on sibling caries level should be routinely combined with clinical evaluation to identify children at risk. Moreover, information on social and family conditions should be used to target prevention and health promotion at the school or municipal level. These approaches could possibly contribute to reducing the existing caries inequalities.